Improving Natural Science Learning Outcomes Through Problem Based Learning To Fourth Grade Student Of SDN Blagung - Diyah Hayu Setianingsih (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to determine whether the application of the Problem Based Learning (PBL) learning model can improve science learning outcomes for fourth grade students at SD Negeri Blagung. This research type is a Classroom Action Research which is carried out in 2 cycles. The research subjects were 19 students in grade IV at SDN Blagung, consisting of 9 male students and 10 female students. Data collection techniques using observation, test, and documentation. The results of the research show that the implementation of Problem Based Learning (PBL) model can improve the science learning outcomes of fourth grade students at SDN Blagung. The results showed that there were 5 students (26%) who completed the pre-class, increased to 12 students (63%) in cycle I and increased to 18 students (95%) in cycle II. From the results of this study, it can be concluded that the application of Problem Based Learning (PBL) model can improve learning outcomes in natural science dealing with objects transformation material.